Dynamics of usage of menstrual hygiene and unhygienic methods among young women in India: a spatial analysis - Trupti Meher; Harihar Sahoo (BMC, 2023)
Abstract Background Menstruation, especially the menstrual cycle, is a vital sign for female adolescent health and maintaining menstrual hygiene is of utmost importance for menstruating girls and women. However, menstrual hygiene and management are issues that have not received adequate attention. Therefore, the present study aimed to explore spatial patterns of menstrual hygiene practices in India and to identify their socioeconomic and demographic determinants among women aged 15-24 years. Methods The study utilized data from the fifth round of the National Family Health Survey (NFHS-5) conducted during 2019-21 in India. The analysis was limited to 241,180 women aged 15-24 years. The statistical methods range from multinomial logistic regression, spatial autocorrelation in terms of Moran's I statistics, to spatial regression in order to understand the spatial dependence and clustering in different methods of menstrual practices across the districts of India. Results Almost half of the respondents (49.8 percent) reported using hygienic methods of bloodstain protection, while 22.7 percent still relied on unhygienic methods and 27.5 percent reported using both hygienic and unhygienic methods during their menstruation. Factors like age, place of residence, caste, religion, education, wealth index and toilet facility were found to be significantly associated with the use of unhygienic and both methods. It was also observed that the percentage of women practicing hygienic methods was predominantly higher in the Southern region. On the other hand, states like Madhya Pradesh and Bihar appeared to be hotspots for unhygienic menstrual practices. The univariate Moran's I value for unhygienic and both methods were 0.722 and 0.596, respectively, depicting high spatial autocorrelation across districts in India. In spatial regression, rural residence, illiteracy, poverty, and no toilet facility were found to be statistically significant predictors of the use of unhygienic method and both methods. Conclusion Young women should be educated about the importance of menstrual hygiene practices and the physiological consequences of unhygienic practices. Furthermore, interventions should target socio-economically disadvantaged women to increase the use of sanitary napkins.